On the Combined Application of Iatroscan TLC-FID and GC-FID to Identify Total, Neutral, and Polar Lipids and Their Fatty Acids Extracted from Foods. (15th January 2013) - Sinanoglou, Vassilia J.; Strati, Irini F.; Bratakos, Sotirios M.; Proestos, Charalampos; Zoumpoulakis, Panagiotis; Miniadis-Meimaroglou, Sofia
Abstract : An efficient separation and quantification of the individual neutral and polar lipid classes and their constituent fatty acids was achieved by the combination of two different detection techniques: Iatroscan TLC-FID and GC-FID. The solvent composition and ratio of development system, the sample size, the fidelity, and precision were tested in order to estimate the effectiveness of separation of individual neutral and polar lipid classes and the quantitative reproducibility of the Iatroscan TLC-FID technique. GC-FID method, with a high-quality capillary column, allowed sensitive and reproducible fatty acid qualitative and quantitative analyses, separation of fatty acid structural isomers (e.g., n-C16:0, iso-C16:0 and anteiso-C16:0), positional isomers (e.g., C18:1 ω -9 and C18:1 ω -7), geometrical isomers ( cis-trans ), and homologues (e.g., C16:0, C17:0, C18:0, etc.) in standards and complex lipid samples. Seventeen (17) lipid classes and fifty-two (52) saturated (SFA), monounsaturated (MUFA), and polyunsaturated (PUFA) fatty acids were identified and quantified, respectively, in samples of standard lipid and fatty acid mixtures, simulating the composition of natural lipids and their fatty acid methyl esters in common foods. The wide number of applications establishes this combination of Iatroscan TLC-FID and GC-FID methods as a powerful tool for lipid class and fatty acid analysis of any fat origin.